Meningkatkan Kualitas Kerja melalui Integrasi Akhlaq dan Hukum Islam - Sumarta, Sumarta (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2023)
The integration of Islamic ethical values (akhlaq) and Sharia law into business management holds significant potential for enhancing employee work quality and overall organizational performance. In the context of the complex and diverse modern business environment, these values offer valuable ethical and moral guidance, shaping a strong and sustainable organizational culture. This study reveals several important aspects related to the impact, challenges, and implementation strategies of integrating Islamic values in business management, making it relevant for organizations seeking a more holistic and ethical approach in their operations. The research aims to investigate how the integration of akhlaq and Sharia law can improve work quality in a business context. Using a qualitative approach, data was collected through employee interviews and content analysis. Findings indicate that the application of akhlaq and Sharia law principles within corporate culture can result in a more ethical, integrity-driven, and value-oriented work environment. Employees involved in business practices based on akhlaq and Sharia law tend to be more inspired, productive, and have higher job satisfaction. Some challenges in this integration include a lack of understanding of Islamic principles and resistance to cultural change. However, with appropriate education and training, along with support from company leadership, the integration of akhlaq and Sharia law can become a key factor in improving work quality and creating a sustainable work culture.